PENGARUH PROMOSI MELALUI MEDIA SOSIAL INSTAGRAM TERHADAP MINAT BELI DI NORTHEAST COFFEE PADANG - Dinda Srinovita Dewi; Nidia Wulansari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This research started due to the lack of visit rates and the lack of interest of Instagram followers in promotions carried out by social media at Northeast Coffee. This can be concluded from the many problems found in Northeast Coffee which have not been maximally resolved properly, one of which is that the promotions carried out by Instagram Northeast Coffee have not been effective so that followers are less interested in buying their products. The purpose of this study was to analyze the impact of social media promosi on purchase intention. The type of research used in this research is descriptive with quantitative data. The type of data used in this research is primary and secondary data. The population of this research is visitors who come to Northeast Coffee. The research sample is 97 consumers Sampling techniques using targeted sampling techniques. The research method was performed using a questionnaire (questionnaire) with a Likert scale to check validity and reliability. Data for this study were processed using SPSS 25.00. The results of this study indicate that promotions are in a fairly good category, namely 5.76%. And the buying interest variable is in a pretty good category, namely 75.26%. The effect of promotion (X) on buying interest (Y) with a score of 9.9% and 90.1% Affected by other factors. Furthermore, a simple linear regression analysis gave an F number of 10,441 in sig. 0.000 < 0.05.